MY SAY: AIG and harakiri - Abd Razak, Dzulkifli (2009)
On an international flight recently, I watched a movie by Bernard Emond entitled Contre toute Esperance. It revolved around switchboard operator Réjeanne Poulin who loses her job when the company decides to sell its interest to another US company called WorldMart. In the transaction, employees like Réjeanne have to opt for several lowpaying jobs to make ends meet while their boss collects millions in compensation.